2013
DOI: 10.1080/10810730.2013.778360
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Information Seeking Among Jewish and Arab Adolescents in Israel: Results From a National School Survey

Abstract: This study examined patterns and determinants of seeking online health information among a nationally representative sample of 7,028 Jewish and Arab 7th- through 12th-grade students in 158 schools in Israel. Nearly all respondents (98.7%) reported Internet access, and 52.1% reported having sought online health information in the past year. Arab students (63%) were more likely than Jewish students (48%) to seek online health information. Population-group and sex differences in health topics sought online were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 42 publications
5
36
0
Order By: Relevance
“…Studies have reported that Arab teenagers in Israel have extensive access to the Internet and Facebook (Abbas, 2010;Neumark et al, 2013). In a study that investigated differences in the use of computer-mediated communication (CMC) in Israel, Mesch (2011) found that Arabs were more likely to use CMC to expand their business and occupational contacts, whereas members of the majority Jewish group were more likely to use CMC to maintain existing family and friendships ties.…”
Section: The Israeli Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that Arab teenagers in Israel have extensive access to the Internet and Facebook (Abbas, 2010;Neumark et al, 2013). In a study that investigated differences in the use of computer-mediated communication (CMC) in Israel, Mesch (2011) found that Arabs were more likely to use CMC to expand their business and occupational contacts, whereas members of the majority Jewish group were more likely to use CMC to maintain existing family and friendships ties.…”
Section: The Israeli Contextmentioning
confidence: 99%
“…Trust is another important aspect that is also shaped by cultural values and influences the motivations for Facebook use (LorenzoRomero & Constantinides, 2011;Neumark, Lopez-Quintero, Feldman, Hirsch Allen, & Shtarkshall, 2013;Sledgianowski & Kulviwat, 2009;Vance, Elie-Dit-Cosaque, & Straub, 2008). Trust plays a central role in high context cultures such as the Arab one (Al-Haj, 1995;Hall, 1976;Hofstede, 1980aHofstede, , 1980bTriandis, 1989Triandis, , 1995Zakaria et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While many information-seeking adolescents access OHI by going directly to specific health websites and portals, a much greater proportion (70%) seek information using search engines, primarily Google.co.il, Finder, and Kafe [41]. About one third (35%) of the adolescent Internet users reported being aware of the problematic nature and biases of OHI, but few view online information critically.…”
Section: Introductionmentioning
confidence: 99%
“…For example, demographic, psychological, socio‐cultural, and source‐, system‐ and content‐related aspects have been found to explain individuals' information seeking and use in a number of quantitative investigations (e.g., Al‐Samarraie, Eldenfria, & Dawoud, ; Khosrowjerdi & Sundqvist, ; Niu & Hemminger, ; Rowley, Johnson, & Sbaffi, ; Zimmer & Henry, ). Several studies bring forth culture as an antecedent of information related activities (Catellier & Yang, ; Jemielniak & Wilamowski, ; Neumark, Lopez‐Quintero, Feldman, Hirsch Allen, & Shtarkshall, ; Oh & Kim, ; Yoon & Kim, ). An overarching definition depicts culture as “the set of shared attitudes, values, goals, and practices that characterizes an institution … a racial, religious, or social group” (Merriam‐Webster Dictionary, ).…”
Section: Introductionmentioning
confidence: 99%